Proposal for ecological corridors for the protection of the jaguar in Western Ecuador - Barros-Diaz, Cristian; Pérez-Correa, Julián (Revista de Biología Tropical, 2024)
Introduction: Biodiversity conservation and ecosystem preservation have become a challenge today due to increasing habitat loss and forest fragmentation. Objective: To propose an ecological corridor for the recolonization of the jaguar (Panthera onca) and its prey. Methods: Western tree cover was calculated using Hansen Global Forest Watch data in Google Earth Engine, then Wallace was used to make potential distribution models with data on the presence of four species of jaguar prey (Cuniculus paca, Dicotyles tajacu, Mazama gualea and Odocoileus virginianus) and then mapped in Qgis. Results: The tree cover of Western Ecuador has experienced a loss of 406 145 hectares in the last 21 years. Of the 80 models generated in 2022, the Quadratic 3.0 model was chosen as the best. Overlaying the model in QGIS and using the shapes of the protected areas of Western Ecuador, the proposal of the corridor was plotted. The study proposes an ecological corridor focused on areas with high habitat quality and ecological connectivity, considering the results obtained in tree cover and the modeling of jaguar dams will serve as a guide for organizations and national authorities and as a proposal to generate ecological corridors closer to the reality of habitat availability in other countries. Conclusion: This ecological corridor is necessary to facilitate the movement and dispersal of species that could benefit from its existence, both between different habitats and protected areas, which would be expected to favor the recolonization of the jaguar and contribute to the maintenance of the genetic diversity of the populations.